Incomplete phase separation strategy to synthesize P/N co-doped porous carbon with interconnected structure for asymmetric supercapacitors with ultra-high power density. (1st March 2019) - Wang, Ni; Wang, Chenzhe; He, Lixiang; Wang, Yang; Hu, Wencheng; Komarneni, Sridhar
Abstract: Herein, we propose a facile incomplete phase separation strategy unlike the tedious synthesis approaches of the past to fabricate P/N co-doped porous and interconnected carbon (PNPC) particles with a specific surface area (SA ) of 1920 m 2  g −1 . The heteroatom doped porous carbons were demonstrated to possess improved conductive property and excellent stability for supercapacitor application. The PNPC bunch delivered a high specific capacitance of 318 F g −1  at 1 A g −1 and a remarkable cycling stability, i.e., 96.2% initial capacitance after 10, 000 cycles in 6 M KOH electrolyte solution. In addition, an asymmetric supercapacitor (ASC) employing LaNi0.5 Co0.5 O3 /0.333Co3 O4 hollow spheres with a mesoporous shell as a positive electrode and PNPC bunch as a negative electrode showed a maximum specific capacitance of 109.6 F g −1  at 1 A g −1 in a potential window of 0–1.7 V. More importantly, the reformative ASC can be discharged up to 0.5 s at a charge current density of 1 A g −1 to deliver an ultrahigh power density of 89.7 kW kg −1, much higher than those of the reported ASCs. This exciting result paves a way for practical application in high power devices. Graphical abstract: Highlights: A facile incomplete phase separation strategy to fabricate doped porous carbon. The sample delivers a high specific capacitance of 318 F g −1  at 1 A g −1 . The assembled ASC exhibits a specific capacitance of 109.6 F g −1  at 1 A g −1 in 0–1.7 V. An ultra-high power density of 89.7 W kg −1 can be addressed.